2021
DOI: 10.3390/ma14143790
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Na+ Ion Conductivity of Stoichiometric Na3Zr2Si2PO12 by Liquid-Phase Sintering with NaPO3 Glass

Abstract: Sodium super ionic conductor (NASICON)-type Na3Zr2Si2PO12 (NZSP) with the advantages of the high ionic conductivity, stability and safety is one of the most famous solid-state electrolytes. NZSP, however, requires the high sintering temperature about 1200 °C and long sintering time in the conventional solid-state reaction (SSR) method. In this study, the liquid-phase sintering (LPS) method was applied to synthesize NZSP with the use of NaPO3 glass with a low glass transition temperature of 292 °C. The formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 43 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…[75] For a typical six basal planes in the rhombohedral structure, when there were one phosphorous and two silicon, the Na + conductivity could be promoted due to low energy barriers, which resulted from stronger coulombic repulsion of Na + /P 5+ than Na + /Si 4+ . In addition, the sodium was easy to volatile after calcined at high temperature, so excess Na 2 CO 3 , Na 2 O, [76] or other sodium compounds [77][78][79] were added to Na 3 Zr 2 Si 2 PO 12 to maintain the stoichiometric ratio. The incorporation of excess Na could increase the bottleneck size of the conducted channels and enhance the grain conductivity, and small extra quantities of sodium were beneficial for decreasing NASICON crystallization temperature and reduction of the appearance of ZrO 2 crystalline secondary phases.…”
Section: Namentioning
confidence: 99%
See 2 more Smart Citations
“…[75] For a typical six basal planes in the rhombohedral structure, when there were one phosphorous and two silicon, the Na + conductivity could be promoted due to low energy barriers, which resulted from stronger coulombic repulsion of Na + /P 5+ than Na + /Si 4+ . In addition, the sodium was easy to volatile after calcined at high temperature, so excess Na 2 CO 3 , Na 2 O, [76] or other sodium compounds [77][78][79] were added to Na 3 Zr 2 Si 2 PO 12 to maintain the stoichiometric ratio. The incorporation of excess Na could increase the bottleneck size of the conducted channels and enhance the grain conductivity, and small extra quantities of sodium were beneficial for decreasing NASICON crystallization temperature and reduction of the appearance of ZrO 2 crystalline secondary phases.…”
Section: Namentioning
confidence: 99%
“…[119] In addition, NaPO 3 glass exhibited low glass transition temperature, therefore NaPO 3 was often used as additives to synthesize the Na 3 Zr 2 Si 2 PO 12 , and achieved low sintering temperature and a decrease of grain barrier. [79] In summary, three common methods were utilized to improve the bulk of the electrolyte: novel sintering technologies with low sintering temperature and remaining time, chemical doping, and chemical additives. These methods mainly focused on increasing of Na + concentration and modifying the grain boundary to decrease the grain boundary resistance.…”
Section: Chemical Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ji et al . proposed using NaPO 3 glass as raw materials to synthesize NASICON so as to promote the ion conductivity to 1.81 × 10 –3 S cm –1 . Meanwhile, it is worth noting that the latest research showed that La 2 O 3 can also have a similar effect as flux by adjusting the grain boundary chemical composition to improve the relative density .…”
Section: Introductionmentioning
confidence: 99%
“…proposed using NaPO 3 glass as raw materials to synthesize NASICON so as to promote the ion conductivity to 1.81 × 10 −3 S cm −1 . 19 Meanwhile, it is worth noting that the latest research showed that La 2 O 3 can also have a similar effect as flux by adjusting the grain boundary chemical composition to improve the relative density. 20 Sun et al fabricated La ions containing Na 3 Zr 2 Si 2 PO 12 electrolytes and proved that the introduced La 3+ ions exist in the form of phosphate impurities Na 3 La(PO 4 ) 2 , which can promote ceramic densification and increase the Si/P ratio in the NASICON phase.…”
Section: ■ Introductionmentioning
confidence: 99%